The utilization of primary care and emergency services in the sus of belo horizonte: health problems, procedures and choice of services - Pires, Maria Raquel Gomes Maia; Göttems, Leila Bernarda Donato; Cupertino, Tiago Vilela; Leite, Lucas Simões; Vale, Luciana Ribeiro do; Castro, Marcelo Augusto de; Lage, Ana Carolina Alves; Mauro, Túlio Gomes da Silva (Saúde e Sociedade, 2013)
The use of the Primary Care and Emergency Units of Sistema Único de Saúde (SUS - Brazilian National Health System) was evaluated in the city of Belo Horizonte (Southeastern Brazil). Objectives: to identify the main health problem that the citizen takes to the Emergency Unit and to the Primary Care Unit, considering the specificities of the health care levels; to characterize the main primary level and second level procedures that are used in these services, comparatively. This is a survey in which a closed questionnaire was administered to 997 interviewees from 10 Primary Care Units and 7 Emergency Units. The demand that arrives at the investigated services is for medical consultations and nursing procedures, motivated by minor affections which can be assisted in the Primary Care Unit. Users go to the Primary Care Unit because it is a service that is close to their homes and provides quick assistance, characterizing good offer and capillarity of the Family Health Program. Duplicity in services utilization was verified, which contributes to further investigations.